Modeling the Organizational Agility in the Architecture, Engineering, and Construction (AEC) Industry - Sadikoglu, Emel; Ozorhon, Beliz (IEEE-Inst Electrical Electronics Engineers Inc, 2022)
In today's complex, dynamic, and uncertain business environment with increasing globalization, extreme competitiveness, and changing stakeholder needs, companies are expected to sense the change and respond appropriately. Agility is a significant concept that helps organizations survive, sustain as an operable entity, stay competitive, and become successful in a changing environment. Unlike the other sectors, agility has not been studied in detail in the architecture, engineering, and construction (AEC) industry. This article aims to investigate organizational agility of the AEC companies. In this respect, it proposes a model that includes the following components: organizational agility drivers (political, economic, social, technological, environmental, legal changes, the threat of new entrants, and rivalry among competitors), enablers (flat structure, changed culture, organizational learning, people, technology, and external relations), and capabilities (sensing, responsiveness, flexibility, and competency). The data to verify the model are collected from companies based in Turkey through an online questionnaire survey and analyzed by using structural equation modeling. According to the analysis results, the influence of agility drivers has not been found significant, changed culture directly contributes to higher levels of organizational agility, and responsiveness and flexibility are the major indicators of organizational agility. This study recommends the AEC companies to observe environmental changes and develop strategies enhancing the organizational agility enablers to address these changes.
Keywords: Capabilities; construction industry; drivers; enablers; organizational agility; structural equation modeling (SEM)